The Use of Digital Media "Tayo Prenatal" on Anxiety Pregnant Women - Pratiwi, Dian; Lalita, Elisabeth; Donsu, Amelia; Olii, Nancy (JURNAL INFO KESEHATAN, 2023)
Globally, people are experiencing increased feelings of stress, anxiety, and depression as a consequence of the situation that has arisen due to the current pandemic. Pregnant women also often feel anxious and afraid of being exposed to COVID-19, which has an impact on anxiety and mood disorders. Yoga is an ancient way of living in harmony with oneself (body, emotions, and mind) and nature and can improve individual health and reduce stress. This study aims to determine the average difference in anxiety in pregnant women after being given "prenatal tayo". This research is a quasi-experiment using a pretest-Posttest Control Group Design, with 25 respondents fulfilling the inclusion and exclusion criteria. The inclusion criteria in this study were pregnant women with gestational ages between 14 and ≤ 30 weeks, being able to read and write, and owning a smartphone. Exclusion criteria in this study were pregnant women with pregnancy complications and pregnant women with a history of previous miscarriages caused by a weak uterus or heart disease. The sampling technique is purposive sampling. Statistical tests using independent T test and Paired T-Test. There is a difference in the anxiety of pregnant women before and after being given "Tayo Prenatal". More research is needed regarding changes in anxiety in pregnant women measured every week to determine the effect of the intervention of giving "Tayo Prenatal" compared to giving Yoga.